Fabrication of aneurysm blood vessel siliconephantom using 3D printed semi-reusable mould - Azam Ahmad, Bakir; Mohd Jamil, Mohamed Mokhtarudin; Nasrul Hadi, Johari (Faculty Mechanical Engineering, UMP, 2025)
Aneurysms are vascular diseases with a low survival rate. Studying blood flow characteristics is essential to understand the disease, which would require experimentation on an anatomical phantom structure for simulating and measuring blood flow under controlled conditions. Conventional phantom fabrication often relies on single-use moulds, which are economically ineffective and time-consuming especially when replication is needed. In this study, we developed a method for fabricating an aneurysmal vascular phantom using a 3D-printed semi-reusable mould. The novelty lies in the reusable outer mould cope that was 3D-printed using polylactic acid (PLA), while the inner core was 3D-printed using water-soluble polyvinyl alcohol (PVA). A silicone-based elastomer, Sylgard 184 was used to create the vascular phantom because it approximates the mechanical properties of actual blood vessels. The silicone was injected onto the mould and the PVA core was dissolved in hot water to create a hollow structure. The resulting phantom is elastic and translucent, suitable for macro-scale flow visualization. It is also fabricated at a lower cost than those reported in previous studies. The semi-reusable mould concept enhances scalability by being low-cost and enables repeatable phantom production, offering an efficient way for research, training, and medical device testing.